JUAL BELI BERBASIS HUTANG DAN TANTANGAN PRINSIP TUNAI DALAM FIKIH MU‘ĀMALAH PADA PRAKTIK PERDAGANGAN SYARIAH MODERN - Mahril Rizkana Putra (Mukhtasab: Journal of Economics and Islamic Business, 2026)
The increasing prevalence of debt-based sales has become an inseparable feature of modern economic development, including within contemporary Islamic trade. Transactions that were traditionally conducted on a cash basis have gradually shifted toward deferred payment and installment systems, which are now widely normalized through various contractual arrangements. This shift poses conceptual challenges within fiqh al-mu‘āmalah, particularly regarding the position of the cash principle, which classical jurisprudence regards as a normative foundation for ensuring contractual clarity, certainty of ownership, and transactional justice. This article aims to examine debt-based sales practices in modern Islamic trade and to assess the relevance of the cash principle in preserving the substantive values of Islamic commercial law. This study employs a qualitative normative research method using the approaches of fiqh al-mu‘āmalah and Islamic economics. Data were collected through library research and documentation of transactional practices, classical fiqh texts, fatwas, regulatory frameworks, and contemporary Islamic economic literature. The data were analyzed using normative and comparative techniques to evaluate the conformity of non-cash sales practices with Sharia principles. The findings reveal that debt-based sales have become the dominant pattern in modern Islamic trade, leading to a gradual shift from real exchange transactions toward long-term financial obligations. While the cash principle remains formally acknowledged, its substantive role has been significantly reduced in practice. This study argues that the cash principle remains highly relevant as a normative and ethical benchmark for assessing transactional justice. The implications of this research highlight the need to reinforce the substantive framework of fiqh al-mu‘āmalah so that contemporary Islamic trade practices remain aligned with the objectives of justice and public welfare in Islamic economics.